CROPLAND INTENSIFICATION, SOIL FUNCTIONAL DECLINE, AND PATHWAYS TO SUSTAINABLE CLIMATE-SMART AGRICULTURE, AND FOOD SECURITY IN SOUTHWESTERN NIGERIA: A BIOGEOPEDOLOGICAL APPRASAL - Babatunde, Caleb Ayomide; Nurudeen, Owolabi Oladeji; Olorunsola, Rotimi Babafemi (FUDMA JOURNAL OF SCIENCES, 2025)
Cropland intensification has become a dominant feature of land use in Southwestern Nigeria, driven by population growth, food demand, and urban expansion. However, the sustainability of this intensification is increasingly questioned due to its adverse effects on soil functional attributes. This review examines how cropping patterns and land use transitions are affecting soil biogeochemistry and pedology in the region’s diverse agroecological landscapes. Findings reveal that continuous cropping, monocultures, reduced fallow cycles, and indiscriminate agrochemical use are leading to severe organic matter loss, nutrient imbalance, acidification, and microbial suppression. These biogeochemical disruptions reduce soil fertility, carbon storage, and resilience. Pedologically, intensification causes horizon truncation, profile simplification, erosion, and eventual reclassification of soils from Alfisols and Ultisols to less developed forms. Urban and peri-urban farming also introduces salinity and heavy metal concerns. Despite these challenges, integrated systems—such as agroforestry, legume rotations, and organic input use—offer viable pathways to restore soil functionality. However, research gaps remain in regional-scale assessments, long-term monitoring, and farmer-inclusive soil management. The review concludes by emphasizing the need for soil-informed land use planning and integrated restoration strategies to ensure sustainable intensification and long-term land productivity in Southwestern Nigeria.